Does the Chinese Diaspora Speed Up Growth in Host Countries?. (December 2015) - Priebe, Jan; Rudolf, Robert
Highlights: New, enhanced data set on overseas Chinese covering 147 countries and four decades. We find a positive impact of overseas Chinese on host countries' economic growth. The effect is transmitted via increased trade openness, investment rates, and TFP. Summary: We compiled a new, enhanced data set on the population share of overseas Chinese covering 147 countries over the period 1970–2010. Linking the migration and economic growth literature, this article attempts to estimate the impact of the Chinese diaspora on economic growth in host countries. Regression results from both, "Barro-type" and dynamic panel data models suggest that a country's initial relative endowment with overseas Chinese is positively related to subsequent growth. Results are robust to a number of sensitivity tests. The effect is transmitted via increased trade openness, enhanced investment, and general TFP effects.